Thermal conductivity of dissociating water—an ab initio study - Martin French (New Journal of Physics, 2019)
The thermal conductivity of partially dissociated and ionised water is calculated in a large-scale study using density functional theory (DFT)-based molecular dynamics (MD) simulations. In doing so, the required heat current of the nuclei is calculated by mapping the effective particle interactions from the DFT-MD simulations onto classical pair potentials. It is demonstrated that experimental and theoretical thermal conductivity data for liquid heavy water and for ice VII are well reproduced with this efficient procedure. Moreover, the approach also allows for an illustrative interpretation of the characteristics of the thermal conductivity in the dense chemically reacting fluid. The thermodynamic conditions investigated here range from densities between 0.2 and 6 g cm ^−3 and temperatures between 600 and 50 000 K, which includes states highly relevant for understanding the interiors of water-rich planets like Uranus and Neptune and exoplanets of similar composition.